The Influence of Foreign Direct Investment on the GDP Progression of Pakistan - Muhammad Aslam Javed (STIM LASHARAN JAYA MAKASSAR, 2020)
The Foreign Direct Investment (FDI) inflows play a very important role in the economic development of the beneficiary country. The objective of this study is to check the impact of the exchange rate (and other variables like Foreign Exchange Rate, Consumer price index, Trade Openness, and Energy Imports) on foreign direct investment in Pakistan by taking annual data from the period 1999-2013 (Monthly Basis).By using Descriptive,Correlation and regression , the effect of Consumer Price Index, exchange rate, trade openness, energy imports on Foreign Direct Investment (FDI) of Pakistan. The study guide the foreign investor and to categorize the factors, that can affect the Foreign Direct Investment (FDI), while investing in Pakistan.